BUDIDAYA UDANG VANNAMEI (LITOPENAEUS VANNAMEI) DI LAHAN PEKARANGAN KELURAHAN PAKIS KECAMATAN SAWAHAN KOTA SURABAYA - Achmad Kusyairi; Didik Trisbiantoro; Sri Madyowati (JPM17: Jurnal Pengabdian Masyarakat, 2019)
The increasing cultivation of Vannamei shrimp throughout the archipelago in theaquaculture area lately has made some farmers try to cultivate vannamei shrimp in freshwaterponds, and even exploring farmer groups in urban areas also try to cultivate vannamei shrimp infresh water by utilizing less productive land. Vannamei shrimp that have a high tolerance tosalinity, ie from 2 to 40 ppt, and will even grow quickly at lower salinity. The condition ofshrimp adapted to salinity then made some farmers try to cultivate vannamei shrimp in freshwater through an acclimatization process and successfully carried out shrimp farming at lowsalinity at 2 ppt salinity. Cultivation of vannamei shrimp in fresh water has several advantagesincluding: resistance to the risk of contracting shrimp disease caused by viruses and bacteria thatinfect many shrimp in brackish water. The aim of the activity is to improve the ability andcapacity of the group through counseling and training on how to make good shrimp farming sothat it can increase production efficiency and productivity and minimize the risk of failure ofvannamei shrimp farming. The approach method used to overcome the problems faced by theGotong Royong farmer group is by way of an ongoing participatory approach between theproposing team and partners, as the controller of the Community Partnership program which hasan active role in providing assistance and periodic guidance to partners. From the results of thisactivity the following conclusions were obtained: (1) Cultivation of vannamei shrimp(Litopenaeus Vannamei) on the grounds in the Mutual Cooperation Group was received withgreat enthusiasm, and asked to be accompanied from pond preparation, fry selection, frystocking, monitoring to harvest. (2) The key to the success of shrimp farming in freshwater inurban yards is the selection of fries adapted to fresh water and monitoring water quality andfeeding during cultivation.Keywords: Cultivation, Vannamei, Yard, Intensive, Mutual Cooperation